2022
DOI: 10.1128/jvi.01228-21
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Surveillance Tracks the First Community Outbreak of the SARS-CoV-2 Delta (B.1.617.2) Variant in Brazil

Abstract: As 2021 comes to a close, the advances in vaccination against COVID-19 allow the world to glimpse an end to the pandemic. In Brazil, the disease has cost more than 600,000 lives and affected more than 21 million people. When the second wave of COVID-19 hit in early 2021, the country saw more than 3,500 daily deaths. As Brazil started to recover from this number, the first reports of infection by the Delta (B.1.617.2) Variant of Concern (VoC) in the country were emerging. The first confirmed case of this varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 6 publications
5
24
0
Order By: Relevance
“…One month later, this variant was also detected in other capitals, such as Belo Horizonte, Brasília, and São Paulo. A study using random sequencing of samples from patients with COVID-19 described that community transmission of the Delta in Rio de Janeiro possibly started in June, corroborating the results found in our study [ 36 ]. Our results demonstrated that the Delta VOC had become the predominant variant in several capitals such as Rio de Janeiro, São Paulo, Belo Horizonte, Belém, Porto Alegre (considering the 90% predominance cut-off) in September 2021.…”
Section: Discussionsupporting
confidence: 91%
“…One month later, this variant was also detected in other capitals, such as Belo Horizonte, Brasília, and São Paulo. A study using random sequencing of samples from patients with COVID-19 described that community transmission of the Delta in Rio de Janeiro possibly started in June, corroborating the results found in our study [ 36 ]. Our results demonstrated that the Delta VOC had become the predominant variant in several capitals such as Rio de Janeiro, São Paulo, Belo Horizonte, Belém, Porto Alegre (considering the 90% predominance cut-off) in September 2021.…”
Section: Discussionsupporting
confidence: 91%
“…The need of oxygen and a lethality rate were observed only in the patients infected by the variants. However, these numbers were below the national (Lamarca et al, 2021) and international average for COVID-19 (Graham et al, 2021), which may be connected to the access and quality of the healthcare provided to the patients from this study, who were monitored daily by phone.…”
Section: Discussionmentioning
confidence: 67%
“…The identification of virus variants was made by viral genome sequencing by the Oswaldo Cruz Foundation (FIOCRUZ), Rio de Janeiro, the National laboratory of reference and certified for diagnosis of COVID-19. The methods and techniques for laboratorial diagnostic and sequencing are from national network of surveillance of COVID-19 and were previously published (Faria et al, 2021;Lamarca et al, 2021;Naveca et al, 2021).…”
Section: Study Design and Clinical Samplingmentioning
confidence: 99%
“…Our study pointed out that the respiratory symptoms surveillance system is a useful tool that can prevent the transmission of COVID-19 in a public school in a middle-income country such as Brazil. However, during the study period, the Delta variant, which is highly infective, was predominant in the state of São Paulo [9]; no cases of COVID-19 transmission occurred at school. All employees had been fully vaccinated with two doses of the COVID-19 vaccine, and students were vaccinated with at least one dose of the vaccine, which may have had an impact on the low positivity of the participants.…”
Section: Discussionmentioning
confidence: 90%